Innovation in Baby Massage Services "Rembulan" (Relaxation for Healthy, Active, and Comfortable Growth) to Reduce Stunting Prevalence at Lontar Health Center, Surabaya - Ika Devy Pramudiana; Sri Roekminiati; Nihayatus Sholichah; Sri Kamariyah; Widyawati (International Journal of Scientific Multidisciplinary Research, 2024)
This study aims to explore and analyze the effectiveness of the "Rembulan" baby massage service innovation at Lontar Health Center, Surabaya, in reducing stunting prevalence. This service enhances infant health and well-being through massage methods that support relaxation, optimal growth, and motor development. In the context of efforts to reduce stunting rates, the program focuses on infants and children under two years old who are at risk of malnutrition and growth delay. This research employs a qualitative approach with in-depth interviews, field observations, and secondary data analysis. Respondents include healthcare workers, parents, and stakeholders directly involved in the baby massage service. The results indicate that the "Rembulan" baby massage program increases infants' nutritional intake by boosting appetite, optimizing digestion, and improving sleep quality. These benefits contribute to better growth and development, reducing the risk of stunting. The study concludes that baby massage innovation has significant potential as a non-pharmacological intervention in public health programs. This service is effective when integrated with nutrition education and continuous health monitoring. Proper implementation can make baby massage a comprehensive solution in government efforts to reduce stunting prevalence in Indonesia